Habilidade competitiva e tolerância a herbicidas de cultivares de soja de diferentes décadas - Hartmann, Katia Cristina Dalpiva (2022)
The soybean agronomic performance of can be compromised by several factors, among which, including weed interference. Herbicides are the main control strategy used by farmers, but can cause phytotoxicity to soybeans, with variation between cultivars. It was hypothesized that modern soybean cultivars, due to their greater yield characteristics improvement, would have less capability to withstand weeds interference and less tolerance to herbicides. Three studies were carried out investigating the competitive ability (studies 1 and 2, in the field) and tolerance to herbicides (study 3, in greenhouse and laboratory) of soybean cultivars launched in different decades in Brazil. Studies 1 and 2 evaluated 12 soybean cultivars, launched between 1965 and 2017, regarding their ability to withstand Bidens pilosa and Euphorbia heterophylla interference, correlations between the agronomic characters evaluated and the yield of the cultivars. Study 3 evaluated six soybean cultivars, available for cultivation in the same period, and their tolerance to the herbicide chlorimuron-ethyl and lactofen and the activity of the enzymes superoxide-dismutase (SOD), catalase (CAT) and peroxidase (POX), known for their role detoxifying herbicides. Major differences between the ancient and modern group of cultivars were expressed in the interference of B. pilosa. Modern cultivars under interference with this weed have further reduced the canopy diameter (R1), dry matter (V7), leaf area, number of branches and stem diameter than older cultivars. On the other hand, they increased the diameter of the stem more than the older ones. Losses on soybean cultivars yield due to interference with 40 plants per m2 of B. pilosa fluctuated between 13 and 84% and with 18 plants per m2 of E. heterophylla between 21% and 58%, demonstrating great difference between soybean cultivars in the capacity to withstand interference. In general, the yield and its components loss due to interference with both B. pilosa and E. heterophylla were not related to the year of release of the cultivars. All cultivars reduced their leaf area and dry mass after application of the herbicides chlorimuron-ethyl and lactofen. It was possible to relate, at least in part, the greater development of the plants of the cultivars Bragg and Paraná (ancient), and their tolerance to the herbicides chlorimuron-ethyl and lactofen with the high activity of the antioxidant enzymes SOD, CAT and POX.